Influencing Social and Emotional Awareness and Empathy with a Visual Arts and Music Intervention for Adolescents. Issue 2 (27th April 2020) - Mogro-Wilson, Cristina; Tredinnick, Lorin
Abstract: Art and music create a powerful presence in the lives of youths. Skills gained from participating in the arts can better facilitate social and emotional learning (SEL) such as improving goal setting, increasing empathy, building relationships, and improving decision making. Connect with Kids, an SEL program that focuses on social and emotional skill building through the use of visual arts and music, was implemented in an urban high school in the Northeast. A total of 304 high school students participated in the study. Students from eight classrooms received the intervention ( n = 143); students from another 10 classrooms ( n = 161) comprised the comparison group and did not receive the intervention. The average youth was 14 years old, white, and female. Results indicated that the Connect with Kids program increased positive social and emotional behaviors among students compared with the comparison group. Examining the implications of the intervention advances gaps in the literature on SEL programs, supports integrating SEL programming on music and art in schools, and promotes continued program evaluation of unique SEL programming specifically for high school students.